Plasma Donor-Derived Cell-Free DNA Levels Are Associated With the Inflammatory Burden and Macrophage Extracellular Trap Activity in Renal Allografts - Guo, Luying; Shen, Jia; Lei, Wenhua; Yan, Pengpeng; Wang, Meifang; Zhou, Qin; Wang, Huiping; Wu, Jianyong; Chen, Jianghua; Wang, Rending (Frontiers in Immunology, 2022)
Recent studies have confirmed the role of plasma donor-derived cell-free DNA (ddcfDNA) as a reliable non-invasive biomarker for allograft injury after kidney trans-plantation. Whereas, the variability of plasma ddcfDNA levels among recipients has limited their clinical use. This study aimed to explore the intrinsic factors associated with plasma ddcfDNA elevation by investigating the impact of Banff lesions and inflammatory infiltrates on ddcfDNA levels in kidney transplant recipients. From March 2017 to September 2019, a total of 106 kidney transplant recipients with matched allograft biopsies were included, consisting of 13 recipients with normal/nonspecific changes, 13 recipients with borderline changes, 60 with T-cell mediated rejection and 20 with antibody-mediated rejection. Histologic classification was performed according to the Banff 2017 criteria by two experienced pathologists. Plasma ddcfDNA fractions ranged from 0.12% to 10.22%, with a median level of 0.91%. Banff histology subelements including glomerulitis, intimal arteritis and moderate to severe interstitial inflammation were correlated with increased plasma ddcfDNA levels. The inflammatory cell infiltrate in the allografts was phenotyped by immunochemistry and automatically counted by digital image recognition. Pearson correlation analysis revealed a significant positive correlation between macrophage infiltration in allografts and plasma ddcfDNA levels. Additionally, macrophage extracellular trap (METs) activity was significantly associated with the rise in plasma ddcfDNA levels. Our findings demonstrated that plasma ddcfDNA could reflect the inflammatory state in renal allografts, and suggested the potential role of METs in the pathogenesis of allograft injury.